Digitalization and Civic Participation in Rural Areas. A Systematic Review of Scientific Journals, 2010-2020 - Stein, Veronika; Pentzold, Christian; Peter, Sarah; Sterly, Simone (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
The smart village is digitally networked and participatory. Its “smartness”, in other words, should be based on interaction between technological infrastructures and civic engagement. While this vision has inspired European policymaking and public discourse in recent years, understanding of the interaction between digitalization and civic participation in rural areas remains limited. In order to fill this gap, this paper offers a systematic review of journal contributions situated at the intersection of digitalization, participatory efforts and rural development. Overall, our study shows that digital rural development and its interplay with participation processes is still a niche concern in scientific journals. We find that articles focus primarily on projects seeking to increase broadband capacity. Second, they focus on the spatial characteristics of rural areas, where social relations and intermediaries play an important role. Third, they emphasize the integration of topdown measures with bottom-up initiatives. There is no single, dominant theoretical approach conceptualizing the intertwining of digitalization and civic participation processes in rural areas. It is evident that local social networks are strengthened and maintained through both analogue and digital formats. Furthermore, the literature provides evidence that sustainable forms of digital engagement are based on civil society initiatives that are supported and accompanied by administrative measures.